Eksistensi Bahasa Arab dalam Perkembangan Islam di Era Society 5.0 - Fidddin, Rufhan; Cahyani, Raziqa Diah; Istiqomah, Dhia; Mustofa, Saiful (Prosiding Konferensi Nasional Bahasa Arab, 2023)
Arabic is increasingly present in improving Islamic civilization in the international world along with technological developments. This research aims to reveal the existence of Arabic in the development of Islam in the era of society 5.0. This research method uses a library method sourced from books, journals, proceedings, print media and online media. The data collection technique for this research is by searching for data, reading data, marking data, and narrating data related to information contained in books, journals, proceedings, print media and online media. The results of this research reveal that the existence of the use of Arabic in the development of Islam in the era of society 5.0 includes naqli arguments and aqli arguments which are based on the Koran, hadith and the words of ulama. The role of Arabic in the era of society in religious aspects, scientific aspects and modern technological aspects. Educational institutions that include strategies, methods and media for learning Arabic.